Essays on the role of managers in the digital transformation - Leão, Pablo (2022)
This dissertation explains how managers influence organizations’ digital transformation (DT). Digital transformation is a pressing organizational change process that firms from different industries, regions, and sizes face to remain competitive in the digital era. It brings several new challenges and opportunities for firms that need to develop new capabilities to respond to the changes in their environment. Consistently, scholars from different fields have taken great interest in this process. However, there is still a lack of studies analyzing managers’ influence on firms’ DT process. Managers are likely to influence organizational processes depending on their capacity to make the right decision at the right time. Therefore, they must develop capabilities that support their organizations’ ability to remain competitive in changing environments. Drawing from the upper echelon theory, dynamic capability, and attention-based view, I present three interrelated papers that provide a multi-method and multi-level analysis of the managerial influence on DT. First, since DT is an emergent organizational change process, research at the managerial level has not yet evolved. Therefore, I present a systematic literature review to summarize and analyze the managerial influence on organizational, strategic, and technological change. Then I integrate the results from this mature body of literature with the digital transformation and present a set of propositions that extend our knowledge of managerial influence on organizational change processes. In the second paper, I conduct a multiple case study with Brazilian firms to explain how managers’ capabilities and characteristics can support firms’ DT process. I draw from the dynamic capability perspective, managerial capability, and upper echelon theory and propose a framework highlighting the emergence of three mechanisms that support managers’ capability in the digital era. Finally, in the third paper, I argue that managerial digital attention can influence firms’ strategic change. However, managerial attention can vary according to the manager’s background (e.g., education) and the firms’ intra-organizational relationships (e.g., connection to startups). Thus, I statistically test the impact of managerial digital attention on strategic change. The result from this analysis confirms the influence managers’ cognition has on firms’ strategic change. Moreover, it suggests that firms’ relationship with startups can also influence strategic changes in the context of digital transformation. In contrast, I found no significant moderation of managerial background. Overall, this dissertation results demonstrate that managers can influence change in organizations. However, they must develop new capabilities and adapt existing ones to support their firms’ DT. Such capabilities rely on managerial characteristics (e.g., educational background, experience, and cognition) that enable the emergence of mechanisms that support managers’ ability to sense and seize opportunities and reconfigure organizations’ assets and resources.